2017
DOI: 10.1007/s11665-016-2460-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stitch Yarn on the Delamination Resistance in Non-crimp Fabric: Chemical and Physical Interpretation

Abstract: Low-bandgap organic polymers, poly[(4,4 bis(2 ethylhexyl)cyclopenta [2,1 b:3,4 b′]dithiophene) 2,6 diyl al (2,1,3 benzothiadiazole) 4,7 diyl](PCPDTBT), and poly [(4,4′ dioctyldithieno[3,2 b:2′,3′d] silol 2,6 diyl) alt (2,1,3 benzothiadiazole) 4,7 diyl)], (Si-PCPDTBT) were analyzed at the air-water interface forming a Langmuir monolayer. In order to form stable monolayers and to transfer to solid supports, amphiphilic molecules of stearic acid (SA) were mixed with them. For the pristine polymers, the floating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
1
14
0
1
Order By: Relevance
“…This continues until the elastic energy diminishes and achieves the equilibrium condition, as the energy failure for the surface of the adhesive is less than the first load. Detail A in Figure illustrates the initial rough aspect through the adhesive, which reflects the unstable nature of delamination propagation, which is in accordance to the observation of Shiino and Amaral …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This continues until the elastic energy diminishes and achieves the equilibrium condition, as the energy failure for the surface of the adhesive is less than the first load. Detail A in Figure illustrates the initial rough aspect through the adhesive, which reflects the unstable nature of delamination propagation, which is in accordance to the observation of Shiino and Amaral …”
Section: Resultsmentioning
confidence: 99%
“…During the quasi‐static delamination propagation, the crack migrated from the adhesive layer to the neighboring prepreg layer revealing the difference in the toughness, as seen in Figure A, as the texture in the adhesive is rougher than the prepreg, at which presented smooth surface. These observations are in accordance with Amaral et al and Shiino et al, who related the rough aspect to the increase of SERR. Figure B of the CC joint fracture surface showed the same texture as identified in the crack migration as shown in detail of Figure A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, noncrimp fibers are more expensive than traditional woven roving, thus their application is limited to highperformance composites. Another critical aspect was highlighted by Shiino et al (2017) in delamination problems, which found a decrease in the surface propagation energy because the stitch yarn replaced the carbon fiber/ epoxy interface, which has better chemical affinities.…”
Section: Recent Technological Innovationsmentioning
confidence: 99%
“…There are several manufacturing techniques available for making reinforcement preforms for composite laminates and these include (1) Braiding [80,81], (2) Stitching [82][83][84][85][86][87][88], (3) 3D Z-Pinning [89][90][91], and (4) 3D weaving [92]. The schematic of different types of 3D sandwich structure is depicted in Figure 5.…”
Section: D Sandwich Structuresmentioning
confidence: 99%